Efektivitas Model Pembelajaran LOK-R terhadap Kemampuan Pemecahan Masalah Matematis - Asma Zulfa Habibah (Universitas Pendidikan Ganesha, 2024)
This research examines the stages of the LOK-R learning model in statistics learning and how the LOK-R learning model is applied to students' mathematical problem solving abilities in statistics learning. The aim of this research is to find out what stages go through in learning statistics using the LOK-R learning model and its impact on students' mathematical problem solving abilities. The researcher used a descriptive qualitative research method, carried out with a case study approach. The object of this research was 31 students in class X-11 MAN Sidoarjo for the 2023/2024 academic year. Data was collected through tests, observations and literature studies. After implementing the LOK-R learning model, 100% of students had very high problem solving abilities. Almost all students were able to work on the problems given with perfect levels of problem solving ability, of the total students there were only 14% whose scores were less than perfect. The LOK-R learning model has proven to be effective as a learning innovation to improve students' problem solving abilities in statistics learning. The literacy stage in LOK-R learning hones students' abilities in understanding existing problems. The Orientation Stage hones students' abilities in making plans to solve problems. The Collaboration Stage hones students' abilities in carrying out the completion plans that have been made. Lastly, the reflection stage sharpens students' ability to review the solutions that have been made. Increasing students' problem solving abilities can be seen from increasing student understanding and student learning outcomes.